Eruption Cyst of a Newborn and Review of the Management - Baharin, Fadzlinda; Mohamad Zon, Erinna (IIUM Medical Journal Malaysia, 2023)
Eruption cyst is a cyst associated with the unerupted tooth that is rarely found in a newborn or infant. We reported a case of a male infant who presented with an eruption cyst at birth in which has not caused any feeding or airway problem in him. A periodic monitoring was performed and spontaneous regression of the cystic lesion was observed within a month with the presence of a neonatal tooth .